School Leadership for Decolonization and Indigenization - Hill, Joshua (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation, 2022)
Decolonization and Indigenization of k-12 schooling is pressing and important and must move forward within the significant challenges and unique circumstances of the COVID-19 pandemic. In this paper I share what I learned in partnership with school leaders about leading Indigenization in a global pandemic. Through findings from a design-based study I present the needs and challenges of school leaders and chronicle what school leadership looked like towards decolonization and Indigenization. I conclude with questions intended to inspire critical reflection and open up possibilities for educators, policy makers, and educational researchers leading this work in the ongoing pandemic and beyond.